Effects of hydrotherapy on adaptation following a simulated cycling grand tour - Halson, S. L.; West, N. P.; Bartram, J.; Stephens, J.; Hopkins, W. G.; Martin, D. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Although cold water immersion is beneficial for recovery between bouts of high-intensity exercise, it may impair long term performance by attenuating the stimuli responsible for adaptation to training. Here we report a comparison of effects of cold-water immersion and passive rest on performance over a 39-day training block. Methods: Thirty-four male endurance-trained competitive cyclists were randomized to cold water immersion or control (no recovery) groups for a simulated cycling grand tour consisting of 7 d of baseline training, 21 d of intense training, and an 11-d taper. Criteria for completion of training and testing were satisfied by 10 cyclists in the cold-water immersion group (age, 20.2 ± 1.7 y; mass, 70.9 ± 6.5 kg; maximal aerobic power, 5.13 ± 0.21 W/kg) and 11 in the control group (19.8 ± 1.7 y; 68.9 ± 8.0 kg; 5.01 ± 0.41 W/kg). Cyclists completed two sets of performance tests each week: a combination cycling test consisting of 6-s sprints (MMP1s), a series of varying intervals, and a 10-min time trial on one day, and two 4-min bouts separated by 30 min of recovery (2xMMP4m) the next day. Cold-water immersion was performed 4 times per week for 15 min at 15°C following training and testing sessions. Uncertainty in mean differences between groups in the changes in mean performance power between tests following baseline and taper periods was estimated as 90% confidence limits and evaluated probabilistically in relation to a smallest important effect on mean power of 1%. Results: Cyclists in the cold water group had an unclear change in overall 4-min power relative to control (2.7%, ±5.7%); however when subtracting the power in the first effort from the second effort, the cold water group showed a clear likely beneficial effect compared with control (3.0%, ±3.8%). The change in MMP1s in the cold water group also demonstrated a clear likely beneficial effect compared to control (4.4%, ±4.2%). Observed differences between groups for the 10-min time trial were trivial but the effect was unclear (-0.4%, ±4.3%). Discussion: The primary objective of this study was to evaluate whether cold water immersion during a 3-wk phase of rigorous cycling training (simulating aspects of a Grand Tour) would impair cycling performance. In summary, data from this study do not support recent speculation that cold-water immersion is detrimental to adaptations to 3 weeks of increased training load in competitive cyclists.